Review of Kelawakaju Maddison & Ruiz, 2022 from China, with description of two new species (Araneae: Salticidae: Salticinae) - Yu, Kun; Li, Yijing; Zhang, Junxia (Zootaxa, 2025)
The species of Kelawakaju Maddison & Ruiz, 2022 from China are reviewed, and two new species are described based on both sexes: K. nezha Yu & Zhang, sp. nov. (Yunnan) and K. pomo Yu, Li & Zhang, sp. nov. (Guangxi). K. frenata (Simon, 1901), previously known from China, is further described here for comparison. A key for identifying all species within Kelawakaju is provided.